2022
DOI: 10.1108/jbim-02-2021-0099
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of cultural controls on the relationship between traditional formal sales controls and inside salesperson performance

Abstract: Purpose For the past several decades, the sales control literature has focused on the outside sales context. This study aims to extend sales control research by examining formal and informal sales controls, embodied by cultural controls, used by sales managers in an inside sales context, where the sales agent’s performance focus extends beyond sales outcomes to include the influence of operational phone outcomes. Design/methodology/approach Based on 232 B2C and B2B inside sales agent survey responses, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…Prior sales control literature has examined the relationship between sales controls and autonomous motivation (Küster and Canales, 2011;Miao and Evans, 2014). Conde et al (2022) also support the positive work outcomes of a sales culture grounded in SDT principles. Consequently, the degree to which SDT can be evoked to explain how autonomous motivation as a cultural control can affect overall performance has received little attention in prior sales control research.…”
Section: Sales Controlsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior sales control literature has examined the relationship between sales controls and autonomous motivation (Küster and Canales, 2011;Miao and Evans, 2014). Conde et al (2022) also support the positive work outcomes of a sales culture grounded in SDT principles. Consequently, the degree to which SDT can be evoked to explain how autonomous motivation as a cultural control can affect overall performance has received little attention in prior sales control research.…”
Section: Sales Controlsmentioning
confidence: 99%
“…Similarly, previous research has demonstrated that work environments grounded in autonomous motivation positively influence work outcomes (Ryan and Deci, 2017;Deci et al, 2017). Therefore, the current study is grounded in SDT and examines the mediating effect of autonomous motivation, as a cultural control, on the relationships between traditional outcomes, sales controls and inside sales agents' performance (Conde et al, 2022). The primary research question is: RQ1.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations